Study of antioxidant properties of 7-benzyl-8-benzylidene hydrazine xanthine derivatives in vitro and in vivo - Yevseyeva, L.; Romanenko, M.; Aleksandrova, K.; Ivanchenko, D.; Levich, S. V.; Pavlov, S. V.; Романенко, Микола Іванович; Александрова, Катерина Вячеславівна; Іванченко, Дмитро Григорович; Левіч, Сергій Вадимович; Павлов, Сергій Васильович (Oxidants and Antioxidants in Medical Science, 2017)
Objective: Acute myocardial infarction (AMI) plays a leading role in the structure of morbidity and mortality worldwide. One of the main parts of it pathogenesis is production of reactive oxygen species (ROS). The accumulation of ROS in cardiomyocytes results in lipid peroxidation, protein oxidation, DNA damage, and finally cell death. Thereby the search of novel drugs that have antioxidant activity and can be used to complex treatment of myocardial infarction is reasonable. It is known that xanthine derivatives exhibit a broad spectrum of biological activity including antioxidant so that the aim of this research was to study in vitro and in vivo antioxidant action of derivatives of 7-benzyl-8-benzylidene hydrazine xanthines.
Keywords: acute myocardial infarction; lactate dehydrogenase; protein oxidation; superoxide dismutase; xanthine derivatives